2017
DOI: 10.1016/j.jvs.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Elective Treatment Process for Critical Limb Ischaemia with Tissue Loss: Diabetic Patients Require Rapid Revascularisation

Abstract: Objective: To evaluate treatment outcomes of in situ abdominal aortic reconstruction with cryopreserved arterial allograft (CAA) for patients with abdominal aortic infection.Materials and methods: A retrospective review of prospectively collected data was conducted of patients who underwent in situ aortic reconstruction using CAA for primary, secondary, or prosthetic infection of the abdominal aorta between May 2006 and July 2015, at a single institution. Clinical presentation, indications for treatment, proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 0 publications
2
26
0
1
Order By: Relevance
“…A shorter time to revascularization and less tissue destruction increases the probability of healing of ischaemic foot ulcers . Also, when the delay between specialist assessment to revascularization exceeded 2 weeks, limb salvage was significantly poorer in people with diabetes compared to people without diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…A shorter time to revascularization and less tissue destruction increases the probability of healing of ischaemic foot ulcers . Also, when the delay between specialist assessment to revascularization exceeded 2 weeks, limb salvage was significantly poorer in people with diabetes compared to people without diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that healing progress over the first 4 weeks of treatment significantly predicts healing at 12 weeks among patients with diabetic foot ulcer enrolled in a wound dressing clinical trial . When a vascular consultation is requested, though, it has been shown that limb salvage was less successful in diabetic patients if delayed for more than 2 weeks beyond the first vascular assessment visit …”
Section: Discussionmentioning
confidence: 99%
“…Such a delay, especially in diabetic patients, may lead to poorer leg salvage rates. 26 Therefore, in cases of long infrapopliteal occlusion, the policy at the study clinic is changing to opt for surgical bypass first. This strategy is supported by the present results, showing that, especially in patients with several affected angiosomes and elevated C-reactive protein levels, it seems to be significantly better to perform bypass as a first line treatment and skip the indirect angioplasty.…”
Section: Discussionmentioning
confidence: 99%